Pendampingan Pengolahan Lele Biofok FPST menjadi Produk Abon Di UMKM Desa Batu Kumbung - Topan Siswanto; Nendy Pratama Agusfianto; Armiani; I Made Murjana; Yusi Faizatul Octavia (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi AMM, 2026)
This community service initiative was carried out with MSMEs in Batu Kumbung Village, Lingsar District, West Lombok Regency, West Nusa Tenggara Province. These MSMEs possess significant potential for development into a sustainable, fisheries-based alternative economic source. A key commodity is the catfish, which is widely recognised by the public and boasts high nutritional value. In West Lombok, the Batu Kumbung Village MSMEs focus on processing fishery products into items such as shredded fish (*abon*) and chilli sauce (*sambal*). Additionally, a biofloc pond system managed by the Batu Kumbung Fish Seed Centre (BBI) is utilised for catfish farming. However, the harvest from these ponds has traditionally been sold fresh without further processing, meaning the potential value-added benefits have not been fully realised. As part of this community service project, a team of lecturers from STIE AMM collaborated with the Batu Kumbung Village MSMEs to develop a new processed product: shredded catfish. The initiative included educational sessions and hands-on training in producing shredded catfish, aiming to diversify the MSMEs' product offerings. The project successfully enhanced knowledge and skills regarding catfish processing, which is expected to broaden the product range and boost the competitiveness of the Batu Kumbung Village MSMEs.